1992
DOI: 10.1152/ajpcell.1992.263.1.c220
|View full text |Cite
|
Sign up to set email alerts
|

Citrate transport in proximal cell line

Abstract: Citrate uptake into kidney proximal tubules occurs via an apical dicarboxylate transporter and a poorly characterized process in the basolateral membrane. We used OK cells, a cell line derived from opossum kidney, to study citrate transport in proximal tubule-like cells. Citrate uptake into cell monolayers was studied using [14C]citrate with [3H]mannitol as a volume marker. Citrate uptake into these cells was sodium dependent and saturable with increasing concentrations of citrate. In contrast to previous mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
2
15
2
Order By: Relevance
“…It is unfortunate that NaDC-1 expression is low, making it necessary to transfect the cells with NaDC-1 to study regulation. Our finding of acid regulation is slightly different from what Hamm and colleagues (6,8) found. In their studies using OK cells, acute decreases in pH had no effect on citrate transport, whereas acute increases raised transporter activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is unfortunate that NaDC-1 expression is low, making it necessary to transfect the cells with NaDC-1 to study regulation. Our finding of acid regulation is slightly different from what Hamm and colleagues (6,8) found. In their studies using OK cells, acute decreases in pH had no effect on citrate transport, whereas acute increases raised transporter activity.…”
Section: Discussioncontrasting
confidence: 99%
“…In their studies using OK cells, acute decreases in pH had no effect on citrate transport, whereas acute increases raised transporter activity. As these authors (8) noted, this response to changes in pH is not typical of the proximal tubule apical membrane citrate transporter. In further studies (6), they did find that both acute and chronic (48 h) decreases in media pH increased transporter activity.…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies to investigate proximal tubule citrate transport, our laboratory has used the OK (opossum kidney) proximal tubule cell line (13,21). Our initial cell culture studies demonstrated that citrate uptake in normal calciumcontaining solutions (calcium concentration 1.2 mM) occurred via an apparent tricarboxylate transporter resembling the basolateral uptake of citrate in isolated basolateral membrane vesicles (21,35).…”
mentioning
confidence: 99%
“…In kidney proximal tubules, reabsorption of Krebs cycle intermediates such as citrate, succinate, ␣-ketoglutarate, malate, and fumarate has been shown to be accomplished by Na ϩ -coupled transporters (1)(2)(3)(4)(5)(6)(7)(8)(9). Numerous studies have been performed in intact proximal tubules (10), isolated brush border membrane vesicles (BBMV) 1 (1-5, 11, 12), and basolateral membrane vesicles (BLMV) (12)(13)(14), mostly using citrate or succinate as substrates.…”
mentioning
confidence: 99%
“…The functional differences between BBMV and BLMV transport suggest that there exist different transporter isoforms on the apical and basolateral sides. Also, a possible presence of a trivalent citrate transport system in the basolateral membrane of the proximal tubule cell line from opossum kidney was proposed (9).…”
mentioning
confidence: 99%